1994
DOI: 10.1007/bf00180520
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of prolactinoma patients with the new non-ergot dopamine agonist roxindol: first results

Abstract: We studied the effects of the new non-ergot D2-dopamine agonist roxindol for the treatment of human prolactinomas. Roxindol is a non-ergot drug with additional 5-hydroxytryptamine type 1 A agonist and serotonin reuptake inhibitory activity. Ten patients with prolactin-secreting pituitary adenomas received roxindol three times daily at a dosage of 7.5-30 mg/day for at least 4 weeks according to a prospective protocol. All patients but one had received oral bromocriptine previously without normalization of prola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…Aer the temperature studies, it was observed that 40 C was the most suitable temperature for this reaction. Increasing the temperature above 40 C did not show a signicant improvement but when the temperature reached 60 C, the product efficiency decreased (Table 1, entries [13][14][15][16]. Various piperidine derivatives were successfully prepared from the reaction of benzaldehyde and aniline derivatives, and ethyl/methyl acetoacetate.…”
Section: General Experimental Procedures For the Synthesis Of Piperidinementioning
confidence: 99%
See 1 more Smart Citation
“…Aer the temperature studies, it was observed that 40 C was the most suitable temperature for this reaction. Increasing the temperature above 40 C did not show a signicant improvement but when the temperature reached 60 C, the product efficiency decreased (Table 1, entries [13][14][15][16]. Various piperidine derivatives were successfully prepared from the reaction of benzaldehyde and aniline derivatives, and ethyl/methyl acetoacetate.…”
Section: General Experimental Procedures For the Synthesis Of Piperidinementioning
confidence: 99%
“…Among the nitrogenous cyclic compounds, piperidines and their derivatives have shown impressive biological activity, such as antihypertensive, 5 antibacterial, 6 anticonvulsant, anti inflammatory agents, 7 farnesyltransferase inhibitors, 8 norepinephrine reuptake inhibitor, 9 antipsychotic agents, 10 and antidepressant. 11 In addition, piperidine derivatives act as an important group of therapeutic agents in the treatment of Parkinson's disease, 12 prolactinoma, 13 schizophrenia, 14 influenza infection, 15 cancer metastasis, 16 viral infections including AIDS, 17 obesity, and diabetes, 18 and also play key roles in many disease processes ( Scheme 1 ). 19 Due to the importance of these heterocyclic compounds in terms of the biological and medicinal properties, the introduction of a better and more efficient method for the preparation of piperidine derivatives is in demand.…”
Section: Introductionmentioning
confidence: 99%
“…A new dopaminergic agonist, CV 205-502, is also effective in prolactinoma patients previously intolerant to bromocriptine [10]. Recently, a nonergot DA agonist, roxindol, has also been reported to have a suppressive effect on prolactin secretion in human prolactinomas [11].…”
mentioning
confidence: 99%
“…El costo de los nuevos fármacos y la gran experiencia clínica con bromocriptina, hacen que esta siga desempeñando el principal papel dentro de los agonistas dopaminérgicos en el tratamiento de la hiperprolactinemia (38).…”
Section: Otros Agonistas Dopaminérgicosunclassified